ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA DALAM PEMBERDAYAAN MASYARAKAT (Studi di Desa Simpang Nibung Rawas 2020) - Mellya Embun Baining; Khairiyani; Wiwindari (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis is entitled Analysis of Accountability and Transparency of Village Fund Allocation Management in Community Empowerment in Simpang Nibung Rawas Village in 2020 and aims to determine the accountability and transparency of village fund allocation management at Simpang Nibung Rawas. This study uses a qualitative approach, with data collection methods by conducting observations, interviews, documentation, and supporting tools. From the results of this study it was found that: (1) In the accountability and transparency of the management of village fund allocations in Simpang Nibung Rawas Village that in planning, administration, and accountability for village fund allocations, it has referred to Permendagri No. 113 of 2014. However, transparency has not been fully implemented by the apparatus. the village as the manager of the allocation of village funds to the community in the form of information on the use of village fund allocations. (2) Constraints and efforts to manage ADD in community empowerment in Simpang Nibung Rawas Village, namely low human resources in ADD management. Meanwhile, for ADD management efforts, namely so that the village government pays more attention to, explores innovation and empowers the potential of the community in order to create community welfare independently as stated in the vision and mission of the village.